Haji Hasan Mustapa: Sufisme Lokal dalam Masyarakat Sunda - Acep Aripudin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
The influence of Haji Hasan Mustafa’s (HHM) sufism is clearly seen in the religious practices of Sundanese. However, it is not really clear as a direct influence. The sufism of HHM stands on the basic concept of human and its elements (soul, body and spirit). Although spiritualism developed by HHM is not the only spiritualism developed in Sundanese community, its influences are strong. In fact, HHM’s Sufism has been practiced by Sundanese in their daily ritual activities, particulary by those who lived in villages and in Sundanese’s Dangding and Sinom which are maintained in Sundanese traditional arts. The essence of HHM Sufism can be seen in his writing Martabat Tujuh which could be considered as the peakpoint of HHM’s Sufism thought.